Characteristics of chiropractors who manage people aged 65 and older: A nationally representative sample of 1903 chiropractors. (11th April 2019) - Moore, Craig; de Luca, Katie; Wong, Arnold Y. L.; Fernandez, Matthew; Swain, Michael; Hartvigsen, Jan; Adams, Jon; Peng, Wenbo
Abstract : Objective: To examine the prevalence and profile of chiropractors who frequently manage people aged 65 years and older. Methods: A national cross‐sectional survey collected practitioner characteristics, practice settings and clinical management characteristics. Multiple logistic regression was conducted on 1903 chiropractors to determine the factors associated with the frequent treatment of people 65 years and older. Results: In total, 73.5% of participants report "often" treating those aged 65 years and older. These chiropractors were associated with treating degenerative spine conditions (OR [odds ratio] 2.25; 95% [confidence interval] CI 1.72‐2.94), working in a non‐urban area (OR 1.85; 95% CI 1.35‐2.54), treating low back pain (referred/radicular) (OR 1.74; 95% CI 1.26‐2.40) and lower limb musculoskeletal disorders (OR 1.50; 95% CI 1.15‐1.96). Conclusions: The majority of chiropractors report often providing treatment to older people. Our findings call for more research to better understand older patient complaints that are common to chiropractic practice and the care provided by chiropractors for this patient group.